The RxLR Motif of the Host Targeting Effector AVR3a of Phytophthora infestans Is Cleaved before Secretion. Issue 6 (18th May 2017) - Wawra, Stephan; Trusch, Franziska; Matena, Anja; Apostolakis, Kostis; Linne, Uwe; Zhukov, Igor; Stanek, Jan; Koźmiński, Wiktor; Davidson, Ian; Secombes, Chris J.; Bayer, Peter; van West, Pieter
Abstract : The processing of AVR3a from Phytophthora infestans shows striking similarities to the stepwise modification observed for the PEXEL effectors from the malaria parasite Plasmodium falciparum . Abstract: When plant-pathogenic oomycetes infect their hosts, they employ a large arsenal of effector proteins to establish a successful infection. Some effector proteins are secreted and are destined to be translocated and function inside host cells. The largest group of translocated proteins from oomycetes is the RxLR effectors, defined by their conserved N-terminal Arg-Xaa-Leu-Arg (RxLR) motif. However, the precise role of this motif in the host cell translocation process is unclear. Here, detailed biochemical studies of the RxLR effector AVR3a from the potato pathogen Phytophthora infestans are presented. Mass spectrometric analysis revealed that the RxLR sequence of native AVR3a is cleaved off prior to secretion by the pathogen and the N terminus of the mature effector was found likely to be acetylated. High-resolution NMR structure analysis of AVR3a indicates that the RxLR motif is well accessible to potential processing enzymes. Processing and modification of AVR3a is to some extent similar to events occurring with the export element (PEXEL ) found in malaria effector proteins from Plasmodium falciparum . These findings imply a role for the RxLR motif in the secretion of AVR3a by the pathogen, rather than a direct role in the host cell entry process itself.